Experts, firms, consumers or even hard data? Forecasting employment in Germany. Issue 4 (23rd February 2017) - Lehmann, R.; Wohlrabe, K.
ABSTRACT: In this article, we forecast employment growth for Germany with data for the period from November 2008 to November 2015. Hutter and Weber (2015) introduced an innovative unemployment indicator and evaluated the performance of several leading indicators, including the Ifo Employment Barometer (IEB), to predict unemployment changes. Since the IEB focuses on employment growth instead of unemployment developments, we mirror the study by Hutter and Weber (2015). It turns out that in our case, and in contrast to their article, the IEB outperforms their newly developed indicator. Additionally, consumers' unemployment expectations and hard data such as new orders exhibit a high forecasting accuracy.